A step: Towards a large photometric survey for exoplanets at Dome C - Fressin, F; Guillot, T; Schmider, F; Agabi, A; Moutou, C; Aigrain, S; Bouchy, F; Boer, M; Pont, F; Erikson, A; Rauer, H; Team, STEP (2007)
We present "A STEP" (Antarctica Search for Transiting Extrasolar Planets), a project dedicated to the search for planetary transits from Antartica. The project consists of a semi-automatic ∼40 cm telescope equipped with a 16-million-pixel CCD installed at Dome C. The site offers crucial assets for a ground-based exoplanet transit search: uninterrupted phase coverage, excellent weather, low air-mass variations and reduced scintillation. This system would be able to detect Pegasids transiting in front of stars as faint as magnitude sixteen and could also detect smaller planets in close-in period around brighter stars. This short term project is meant to be a photometric qualifyer for the site and the first stage of a massive detection campaign. A mid-term objective of 1000 detections for 2012 could be achieved either with many small telescopes or with a large Schmidt telescope with a large field of view. The project is relatively simple and cost-effective, and has the double purpose of qualifying the site and obtaining first-class scientific results. Our team is already familiar with transit detection with an automated telescope and cold temperature qualification. © EAS, EDP Sciences 2007.